Inference of gene regulatory network with S-system and artificial Bee Colony algorithm - Obayed Bin Mahfuz (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.